Behaviour of under-track crossings on ballasted railways. (December 2019) - Powrie, William; Le Pen, Louis; Milne, David; Watson, Geoff; Harkness, John
Abstract: Signal and telecommunications (S&T) cables and other services often cross underneath a railway line in a duct or conduit, buried in the ground below the ballast. These under track crossings (UTX) are likely to increase or decrease the track support stiffness compared with the surrounding ground, depending on the material and construction detail of the crossing. This change in support stiffness will give rise to variations in the dynamic loads exerted by moving trains, with the potential to cause track damage. This paper presents measurements of track deflections at two sites associated with different forms of UTX. The data are then used in finite element based vehicle-track interaction analyses to assess the effects of UTX type and construction on track geometry and performance. The results show that poor performance observed at these sites cannot be explained by the difference in support stiffness alone, but follows the development of gaps or voids between the sleeper base and the ballast.